Risk Analysis of Obstructive Sleep Apnea With STOPBANG and Mental Disorders With SRQ-20 in COVID-19 Patients in Regional General Hospital Dr. Saiful Anwar Malang - Laksmi Dewi, Ni Putu; Sri Listyoko, Aditya; Maharani, Iriana (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2023)
Background: On December 31, 2019, a pneumonia outbreak in Wuhan, Hubei, China, was caused by a severe acute respiratory syndrome coronavirus 2 (SARSCoV-2) or Coronavirus disease 2019 (COVID-19). Severely ill COVID-19 patients must be either hospitalized or self-isolated, leading to physical stress from limited space for activities, less social engagement, and anxiety due to the illness. Sleep disorders are widespread among those in self-isolation, with Obstructive Sleep Apnea (OSA) being the most prevalent. External stressors contribute to the development of sleep and mental disorders in people with COVID-19. Objective: To assess the correlation between Obstructive Sleep Apnea and mental problems in COVID-19. Method: Utilized a case-control design with COVID-19 patients hospitalized as cases and persons without confirmed COVID-19 or hospitalization as controls. Result: 70 data points were utilized in this research. There was a significant difference in the risk of Obstructive Sleep Apnea across the groups (p=0.04, r= 5.176). On the other hand, there was no statistically significant difference in mental problems between the groups (p=0.22). Conclusion: A notable disparity among the groups was observed in Obstructive Sleep Apnea, but no significant variance was found in mental problems.